Determination of trace metals in airborne particulate matter of Kuala Terengganu, Malaysia - Mohd Tahir, Norhayati; Poh, Seng Chee; Suratman, Suhaimi; Mohd Ariffin, Marinah; Shazali, N. A. M.; Yunus, Kamaruzzaman (Springer New York, 2009)
Results from the present study in Kuala Terengganu, Malaysia indicated a significant spatial variation but generally the total suspended particulate concentrations (mean = 17.2–148 lg/m3) recorded were below the recommended Malaysia guideline for total suspended particulate (mean of 24-h measurement = 260 lg/m3). Some of the elemental composition of particulate aerosol is clearly affected by non crustal sources, e.g. vehicular emission sources. Based on correlation and enrichment analyses, the elements could be grouped into two i.e. Pb, Cd and Zn group with sources from vehicular emission (r[0.6; enrichment factor[10) and Al, Fe, Mn and Cr group that appears to be of crustal origin (r[0.6; enrichment factor\10). It can also be concluded that the mean levels of Pb (1 ng/m3), Cd (0.02 ng/m3) and Zn (2 ng/m3) in the study area are generallylower than other urban areas in Malaysia (Pb\181 ng/m3; Cd\6 ng/m3; Zn\192 ng/m3).